(Re)discovering the human element in public relations and communication management in unpredictable times - Rodríguez-Salcedo, Natalia; Moreno, Ángeles; Einwiller, Sabine; Recalde, Mónica (Advances in public relations and communication management, 2023)
We live in evolving societies that undergo profound and rapid transformations, and trust and reputation are at risk in a dynamic, disruptive, and uncertain world. How issues are approached in public relations and communication management will determine the future of the field and practice. In this complex scenario, going back to the basic elements of public relations - people and relationships - when managing communications is more important than ever before. (Re)discovering the Human Element in Public Relations and Communication Management in Unpredictable rethinks what it means to put the person at the center of the organization's decisions. The chapters explore different aspects of how public relations and communication management address the challenges of change in unpredictable times, while considering the human element and the people behind communication. The research was selected from a large number of peer-reviewed contributions to the 2021 Annual Congress of the European Public Relations Education and Research Association (EUPRERA), hosted by Universidad de Navarra in Spain. Advances in Public Relations and Communication Management (APCRM) is a publication of the European Public Relations Education and Research Association (EUPRERA). Each volume includes contributions from EUPRERA's annual congress and follow the theme of each event.